AN ANALYSIS OF MODAL AUXILIARY CAN IN THE BOOK OF RULES OF LIFE BY RICHARD TEMPLAR - Edi Purnama; Ravialli Alfaridzi Mahendra (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The title of this research that an analysis of Modal Auxiliary Can in the book of The Way of Life that was written by Richards page 1 to 50. The descriptive method is used in this research. This research uses the theory of Betty Schramfer Azhar. The aim of this research that is to find out how many words modal auxiliary “Can” that it can be found. The taken data is from the book of The Way of Life. The data are selected and analyzed and the result of the research that there are as many as 60 modal auxiliaries and the biggest proportional of modal auxiliary can as ability is the biggest portion 40 modal auxiliaries (67%) and the second is possibility 19 modal auxiliaries (32%) .and the third portion is permission 1 modal auxiliary (1%)